Quantifying the Covalent Functionalization of Black Phosphorus - Wild, Stefan; Xuan Thong Dinh,; Maid, Harald; Hauke, Frank; Abellán, Gonzalo; Hirsch, Andreas (Angewandte Chemie International Edition, 2020)
A straightforward quantification method to consistently determine the overall functionalization degree of covalently modified two-dimensional (2D) black phosphorus (BP) by Raman spectroscopy has been carried out. Indeed, the successful reductive methylation of the BP lattice using sodium intercalation compounds and exhibiting different functionalization degrees has been demonstrated by P-31-magic angle spinning (MAS) NMR spectroscopy. Furthermore, the correlation of P-31-MAS NMR spectroscopy and statistical Raman spectroscopy (SRS) revealed the first method to determine the functionalization degree of BP solely by evaluating the intensities of distinct peaks in the Raman spectra of the covalently modified material, in a similar way to the widely employed I-D/I-G ratio of graphene research.
CRIS-Team WoS Importer:2020-09-18